Moisture Fluctuations, Moisture use and Water Balance under Principal Land Use Systems of Arid Region - Singh, Atar (Annals of Arid Zone, 2016)
In the agroclimate of Pali, Western Rajasthan, moisture in . 0-54 cm soil under c1tivated fallow was 12 percent in rainy season and 8 percent in winter. In crop land moisture fluctuated between 1-2 and 6 percent. Moisture status under grassland and forestry was lower. Maximum (150 mm per year) water use was recorded from grassland followed by cropped land (135 mm), forest and cultivated fallow. July and August were surplus months and water deficiency prevailed during rest of the period.